(untitled) (Global Journal of Medical Research, 1970)
Objectives To describe the sociodemographic characteristics and the findings in the BC screening tests of women who signed up for a Breast Cancer Awareness Month campaign in the Brazilian state of Santa Catarina Methods In this descriptive retros pective observational study 638 women volunteered to participate Sociodemographic and clinical data collection occurred between February 2020 and June 2021 Participants had mammograms and were referred to additional ultrasound exams when necessary All participants with BI-RADS of 4 or 5 were referred to core biopsy Results In our sample 31 2 had had a mammography longer than 5 years or had never had it The most frequent findings in the performed mammograms were dense breasts 37 1 microcalcifications 12 0 and breast lumps 10 4